2001
DOI: 10.1143/jjap.40.2399
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of RhO2 Thin Films by Reactive Sputtering and Their Characterizations

Abstract: Thin films of RhO 2 , which belongs to the family of conducting platinum group metal oxides, were prepared by reactive sputtering. Influences of sputtering parameters, such as rf power and substrate temperature, and postdeposition annealing on crystallinity, chemical bonding state and resistivity of the deposited films were studied, in order to obtain low-resistivity RhO 2 thin films. The resistivity of the deposited films decreased with decreasing rf power. Plasma emission measurement suggested that oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The size of the NPs is affected by the chemical interactions that occur during the ablation process, in turn determined by the liquid environment. As discussed in [ 212 ], XRD and XPS results show that ablation of Rh in water leads to the production of mixed Rh/Rh-oxide phases (RhO 2 and Rh 2 O 3 ), whereas in ethanol essentially metallic Rh NPs are produced, in agreement with [ 216 ].…”
Section: Promising Applications Of Lal Nanostructures For Biotechnsupporting
confidence: 82%
“…The size of the NPs is affected by the chemical interactions that occur during the ablation process, in turn determined by the liquid environment. As discussed in [ 212 ], XRD and XPS results show that ablation of Rh in water leads to the production of mixed Rh/Rh-oxide phases (RhO 2 and Rh 2 O 3 ), whereas in ethanol essentially metallic Rh NPs are produced, in agreement with [ 216 ].…”
Section: Promising Applications Of Lal Nanostructures For Biotechnsupporting
confidence: 82%
“…Previously, we have shown that the RF sputtering of Rh electrode in O 2 on the Rh foil or the inert support (TaO x ) results in the formation of RhO x particles comprising Rh 4+ and Rh 3+ species 9 . The E b (Rh3d 5/2 ) value of these species did not exceed 308.4 eV in good agreement with the literature data 17,18 . The positive shift of the E b (Rh3d 5/2 ) value in comparison with the E b (Rh3d 5/2 ) values typical for Rh 2 O 3 or RhO 2 can be explained by the influence of the RhO x –CeO 2 interaction.…”
Section: Resultssupporting
confidence: 87%
“…9 The E b (Rh3d 5/2 ) value of these species did not exceed 308.4 eV in good agreement with the literature data. 17,18 The positive shift of the E b (Rh3d 5/2 ) value in comparison with the E b (Rh3d 5/2 ) values typical for Rh 2 O 3 or RhO 2 can be explained by the influence of the RhO x -CeO 2 interaction. The E b (Rh3d 5/2 ) > 308.5 eV was observed by many authors who analyzed the properties of Rh/CeO 2 catalysts.…”
Section: Methodsmentioning
confidence: 98%
“…After O 2 exposure, the Rh peak is shifted to a higher BE by 0.3 eV, indicating chemisorption of oxygen on the Rh. The oxygen exposure is not sufficient to completely oxidize the Rh particles, since complete oxidation should result in a 1.0 to 1.3 eV shift in the peak position depending upon Rh oxidation state [29,30]. After the subsequent H 2 exposure, the peak shifts back to the position of the Rh metal state, indicating removal of oxygen from the surface of the Rh particles.…”
Section: Resultsmentioning
confidence: 99%